COLONIZATION'S LINGERING INFLUENCE: EXAMINING THE IMPACT ON INDIAN ENGLISH LITERATURE - Zubair Farooq; Dr. Premchandar P (RADJA PUBLIKA, 2023)
India is a rich site for studying intertextuality and influence due to its contemporary and colonial history of postcolonial culture. British imperialism in India was more pragmatic than other colonial powers, being motivated by economics rather than evangelism. During the emergence of Orientalism, India was the first nation to have a literary impact on the West, but this equation was reversed during colonial intervention. While some critics denounce or acclaim the West's effect on India, Indian writers' responses show complex instances of intertextuality and influence in the form of reception. The literary movement in India has been shaped by the traditional attitudes, culture, social life, and politics of the local people. British rule in India lasted for more than two hundred years and its authority halted the ruling power of the Indian subcontinent. The impact of British colonialism on Indian literature and social life is evident. Understanding English literature history is crucial for understanding English people's way of life, including their educational, social, and cultural attitudes. This research paper examines in detail the effect of colonial rule on English literature in India.